2022
DOI: 10.1111/inm.13089
|View full text |Cite
|
Sign up to set email alerts
|

The perceptions of mental health clinicians integrating exercise as an adjunct to routine treatment of depression and anxiety

Abstract: Individuals with depressive symptoms often experience changes in physical activity and lifestyle factors. Despite the benefits of exercise, mental health clinicians often do not refer for or prescribe exercise as part of traditionally accepted models of care for consumers with depression and anxiety. The aims were to investigate: (i) mental health clinicians' understanding of the relationship between exercise and mental health, (ii) if and how exercise is used by mental health clinicians in treatment for depre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…On average, only 13% of respondents across fve studies had received any formal education in exercise prescription [38,40,42,45,51], and, when asked, almost all respondents stated that they were interested in further training [32,44,45,51]. A similar knowledge barrier was identifed in several qualitative studies [30,31,34,36,39]. Radovic et al [44] found that while 41.2% of participants could identify current physical activity guidelines, only 13.3% could describe them.…”
Section: Lack Of Knowledge and Confdencementioning
confidence: 88%
“…On average, only 13% of respondents across fve studies had received any formal education in exercise prescription [38,40,42,45,51], and, when asked, almost all respondents stated that they were interested in further training [32,44,45,51]. A similar knowledge barrier was identifed in several qualitative studies [30,31,34,36,39]. Radovic et al [44] found that while 41.2% of participants could identify current physical activity guidelines, only 13.3% could describe them.…”
Section: Lack Of Knowledge and Confdencementioning
confidence: 88%
“…Not all barriers to an active lifestyle are related to the patients. Garvey et al ( 24 ) identified barriers to the prescription of exercise on the part of healthcare providers: lack of knowledge on how to prescribe exercise and establish contact with trained physical activity specialists, concerns about the patient’s ability to exercise, risk factors, such as comorbidities, or placing more stressors on their clients ( 24 ). Improvement in cooperation between the different professions is needed in addition to the establishment of routine referral methods with the possibility of individual support for physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Professional assistance in setting goals, overcoming barriers and maintaining motivation ( 17 ), and the inclusion of health care professionals qualified in exercise prescription ( 20 ) are recommended strategies to assist patients with depressive disorder. The importance of increasing autonomous motivation ( 21 ) and self-efficacy ( 22 ) is recognized and Motivational Interviewing techniques can support behavioral change on the basis of patients’ own decisions ( 23 , 24 ). In previous studies, personal or telephone contact provided an opportunity for patients to speak about their goals and any potential reservations regarding exercise ( 25 ), and to explain the effects of physical activity ( 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…The empowerment and support provided by Exercise Physiologists and PHPN to the YMH team were described as contributing to more proactive discussions on the PH of young people with EP. It was recognised in the literature that allied health clinicians may not feel comfortable to provide PH care due to a perceived lack of knowledge and confidence in the PH care domains (Butler et al., 2020; Garvey et al., 2023). Our results highlighted the PHPN has proven to provide great empowerment in encouraging allied health clients to conduct assessments and ensure more are participating in the process.…”
Section: Discussionmentioning
confidence: 99%